Kritik sosial dalam cerita pendek karya Raudal Tanjung Banua - Febriyanto, Dedi; Anista, Eka; Widodo, Mulyanto; Juniar, Elda (Universitas Pendidikan Indonesia, 2021)
This study focuses on the social criticism contained in the short stories by Raudal Tanjung Banua. This research uses a qualitative descriptive method with a sociological literature approach. The research data is in the form of quotations that contain social criticism. Data collection was carried out using a note-taking technique. The data analysis was carried out using Miles and Huberman's theory, namely: (1) identifying short stories, (2) reducing data, (3) presenting data, (4) interpreting data, (5) concluding interpretation results. The results showed that the short stories by Raudal Tanjung Banua contain very complex social criticisms. The social problems that are the target of criticism in the short story include criticism of the hunting of protected animals, humanitarian problems, economic problems, partisanship of the press media, weak principles of religion to the arbitrariness of officials towards the little people. Various social criticisms contained in the short stories can be used as material for reflection for all readers for better changes.